2000
DOI: 10.2307/1593069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mexican Strains of Avian Infectious Bronchitis Isolated during 1997

Abstract: Ten infectious bronchitis virus (IBV) isolates were recovered from broiler chickens in the states of Queretaro and Guanajuato in Mexico. The viruses were isolated from trachea, lung, kidney, and cecal tonsils of birds that showed respiratory signs in spite of vaccination with Massachusetts (Mass) and Connecticut strains of IBV. Each isolate was identified by an accession number from 1 to 10. Six of the isolates were neutralized by Mass monoclonal antibodies, whereas the other four were not. In addition, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Electron microscopy showed only viral particles with morphology consistent with coronaviruses. The molecular reverse-transcriptase-PCR-RFLP pattern of the S1 protein gene was unique for the UNAM-97 IBV variant strain, which differed greatly from those of other strains prevalent in Mexico (Escorcia et al, 2000). This new variant strain was isolated from 5-to 7-wk-old broilers previously vaccinated with Massachusetts and Connecticut IBV strains.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Electron microscopy showed only viral particles with morphology consistent with coronaviruses. The molecular reverse-transcriptase-PCR-RFLP pattern of the S1 protein gene was unique for the UNAM-97 IBV variant strain, which differed greatly from those of other strains prevalent in Mexico (Escorcia et al, 2000). This new variant strain was isolated from 5-to 7-wk-old broilers previously vaccinated with Massachusetts and Connecticut IBV strains.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the use of these IBV vaccines, it is common to find IB problems in immunized chickens, causing a large economic impact. We have previously reported that IBV obtained from trachea, lung, kidney, and cecal tonsil of broiler chickens, and further characterized using the reverse transcriptase PCR and RFLP techniques, showed electrophoretic patterns different from other known IBV isolates (Escorcia et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Elsewhere in Latin America a variant IBV was isolated from commercial chickens in Honduras in 1997 and poor protection against Mass vaccines was demonstrated (Cook et al, 1999). Following the isolation of the Ark serotype in Mexico in the early 1990s (Quiroz et al, 1993), the use of molecular methods subsequently identified IBV variants unique to that country in commercial chickens (Escorcia et al, 2000;Callison et al, 2001;Gelb et al, 2001). They were shown by neutralization tests to be different from Mass or Conn serotypes, but in vivo protection studies were not performed.…”
Section: Latin Americamentioning
confidence: 99%
“…Many of these strains have been related to respiratory diseases (Cubillos et al, 1991;Escorcia et al, 1997;Alvarado et al, 2005;Rimondi et al, 2009), but in Brazil, the strains have been related to enteric problems (Villarreal et al, 2007). Many of these strains have been related to respiratory diseases (Cubillos et al, 1991;Escorcia et al, 1997;Alvarado et al, 2005;Rimondi et al, 2009), but in Brazil, the strains have been related to enteric problems (Villarreal et al, 2007).…”
Section: Occurrence Of Enteric Viruses In Brazilmentioning
confidence: 99%